2016
DOI: 10.1126/scisignal.aad6724
|View full text |Cite
|
Sign up to set email alerts
|

The adaptor protein insulin receptor substrate 2 inhibits alternative macrophage activation and allergic lung inflammation

Abstract: Insulin Receptor Substrate (IRS)-2 is an adaptor protein that becomes tyrosine phosphorylated in response to IL-4 and IL-13 resulting in activation of the PI-3′ kinase/Akt pathway. While the contribution of IL-4 and IL-13 to allergic lung inflammation has been studied extensively, the functional significance of the IRS2 pathway is unclear. To examine the role of IRS2 in allergic disease, we evaluated responses in IRS2-deficient mice. Deficiency of IRS2 resulted in a substantial increase in expression of a subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 66 publications
4
24
0
Order By: Relevance
“…Surprisingly, it was found that mice homozygous for the IL‐4Rα‐F497 mutation exhibited enhanced allergic inflammation, including IgE production, airway hyperresponsiveness, eosinophilic inflammation and mucus production, suggesting a significant contribution of this pathway to the regulation of allergic inflammation in vivo. A similar phenotype of enhanced airway inflammation was also noted in IRS2 –/– mice, implicating IRS2, which is the differentially expressed in hematopoietic cells vs IRS1, in the negative regulatory function of IL‐4Rα‐Y497 . Thus, the precise role of this pathway in modulating the allergic response remains to be fully delineated (Figure ).…”
Section: Il‐4rα Signalling and Mechanism Of Actionmentioning
confidence: 73%
“…Surprisingly, it was found that mice homozygous for the IL‐4Rα‐F497 mutation exhibited enhanced allergic inflammation, including IgE production, airway hyperresponsiveness, eosinophilic inflammation and mucus production, suggesting a significant contribution of this pathway to the regulation of allergic inflammation in vivo. A similar phenotype of enhanced airway inflammation was also noted in IRS2 –/– mice, implicating IRS2, which is the differentially expressed in hematopoietic cells vs IRS1, in the negative regulatory function of IL‐4Rα‐Y497 . Thus, the precise role of this pathway in modulating the allergic response remains to be fully delineated (Figure ).…”
Section: Il‐4rα Signalling and Mechanism Of Actionmentioning
confidence: 73%
“…Indeed, two of four M2 genes were enhanced with p70S6K inhibition, indicating a greater complexity to regulation of M2 gene expression than anticipated. Many M2 genes share common activating and inhibitory pathways (39,40) and can be AKT-dependent or -independent (41). For example, studies of macrophage polarization using macrophages derived from Tsc1 (16, 17)-, Raptor (42)-, and Rictor (16, 42)-deficient mice have con- 1, IL-4 can bind two kinds of IL-4 receptor complexes on monocyte-macrophages, type I (shown here) and type II.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, macrophages that lack IGF1R acquire a more inflammatory phenotype in response to proinflammatory stimuli (4,6). However, IRS2, which mediates both insulin and IGF1 signaling, suppresses alternative activation of macrophages (7). In addition, glucose, insulin, and palmitate treatment of human monocyte-derived macrophages results in a metabolically activated phenotype, a distinct M1 phenotype that is characteristic for proinflammatory ATMs found in obesity (8).…”
mentioning
confidence: 99%